Enhancing young children's science learning through science teachers' formative assessment practices - AlAli, Rommel Mahmoud; Al-Barakat, Ali Ahmad (Frontiers in Education, 2025)
This study aimed to find out how science teachers use formative assessment to enhance children's learning. Data were collected through observing 45 male and female teachers in the classroom using an observation checklist based on international standards to assess teachers' practices in some aspects, such as planning the learning objectives, gathering evidence from activities, providing feedback, self-assessment, peer assessment, and promoting classroom collaboration. The results revealed that teachers' performance in applying formative assessment practices was at a low level across all criteria, as there were weaknesses in planning learning objectives and aligning them with lesson content, as well as a lack of effective use of educational activities to assess student progress. The feedback provided by teachers was insufficient to motivate students to improve their performance, and classroom interaction was limited. Furthermore, there was a lack of opportunities for students to assess themselves and their peers, indicating weaknesses in organizing self-assessment activities. In addition, there were no statistically significant differences in teachers' formative assessment practices based on gender and teaching experience, highlighting the importance of professional development for all teachers to enhance their teaching practices. These results suggest a significant need to improve teachers' skills in applying formative assessment and providing appropriate training.